TRANSFORMING INFORMATION FROM CLIMATE CHANGE NEWS INTO SHORT STORIES FOR LITERARY DIGITAL LITERACY ENHANCEMENT - Inderawati, Rita; Sakdiawati, Sakdiawati; Pratiwi, Weni; Putri, Ermalati; Dari, Tita Ratna Wulan; Fiftinova, Fiftinova (HISKI, 2024)
When we hear the word ‘literature’, we always associate it with old and beautiful things. Climate change is considered as current information that must be understood by everyone and has nothing to do with literature. UNESCO highlights the issue of climate change as an international issue that everyone should be concerned about. Regarding this global issue, UNESCO also puts forward digital literacy involving the ability to use technology, information and communication tools, and involves the ability to learn to socialize, think critically, creatively, and inspire as a digital competition, involving the process of reading, understanding, writing, and composing something as new knowledge or content. This study aimed to discuss how pre-service teachers make short stories using climate change news to enhance literary digital literacy. In other words, students converted news texts about climate change on the internet into short stories. To obtain the data, this study used interview and documentation to analyse the results of students' critical and creative writings in the form of short stories based on climate change in Indonesian context. It is a qualitative and data obtained from student documents were analyzed qualitatively by means of transcription, literature study, and documentation. The results of this study were students be able to write short stories using the news about climate change on the internet facilitated by Canva to produce the learning material and digital story telling. Thus, this climate change-based short stories also contribute to the development of literary digital literacy.Keywords: climate change, utilization, enhancement, short stories, literary digital literacy PENGUBAHAN INFORMASI BERITA PERUBAHAN IKLIM MENJADI CERITA PENDEK UNTUK PENINGKATAN LITERASI DIGITAL SASTRA AbstrakBila mendengar kata sastra, kita selalu mengaitkannya dengan hal-hal lama atau dahulu yang indah. Perubahan iklim dianggap sebagai informasi kekinian yang wajib dipahami oleh semua orang dan tidak ada kaitannya dengan sastra. UNESCO menyoroti isu perubahan iklim sebagai isu internasional yang semua orang harus peduli.Terkait isu global ini, UNESCO juga mengedepankan literasi digital melibatkan kemampuan penggunaan perangkat teknologi, informasi dan komunikasi, dan melibatkan kemampuan untuk dalam pembelajaran bersosialisasi, sikap berpikir kritis, kreatif, serta inspiratif sebagai kompetisi digital, melibatkan proses membaca, memahami, menulis, dan menciptakan sesuatu sebagai sebuah pengetahuan maupun konten baru. Penelitian ini bertujuan untuk mengelaborasi bagaimana mahasiswa calon guru membuat cerita pendek dengan menggunakan konten perubahan iklim untuk mengembangkan literasi digital sastra. Dengan kata lain, mahasiswa mengalihwahanakan teks-teks berita tentang perubahan iklim di internet menjadi cerita pendek. Untuk mendapatkan data, penelitian ini menggunakan instrument wawancara dan dokumentasi hasil tulisan kritis dan kreatif mahasiswa berupa cerpen berbasis perubahan iklim dalam konteks Indonesia. Penelitian ini merupakan penelitian deskriptif kualitatif dan data diperoleh dari dokumen mahasiswa dianalisis secara kualitatif dengan cara transkripsi, studi pustaka, dan dokumentasi. Hasil dari penelitian ini mahasiswa mampu menulis cerpen dengan menggunakan konten atau berita-berita terkait perubahan iklim dengan difasilitasi oleh Canva dan menghasilkan bahan ajar dan cerita digital. Dengan demikian, teks naratif berbasis perubahan iklim ini turut berkontribusi bagi pengembangan Literasi Digital Sastra.Kata kunci: perubahan iklim, kegunaan, pengembangan, cerita pendek, Literasi Digital Sastraa